Zambia Health Sector Public Expenditure Review - Chansa, Collins; Workie, Netsanet Walelign; Piatti, Moritz; Matsebula, Thulani; Yoo, Katelyn Jison (World Bank, Washington, DC, 2019)
The Zambian government has outlined an ambitious rights-based approach to health care provision as outlined in its national health policy. Specifically, the government is determined to achieve universal health coverage (UHC) by providing all its citizens with access to free quality health care services through the public health system. To examine trends and patterns in health expenditures and to identify opportunities for achieving value for money and equity, the Zambian government, with technical and financial support from the World Bank and the U.K. Department for International Development (DFID), conducted a public expenditure review (PER) of the health sector. This review covers 2006−2016 and builds on the PER that was produced in 2009. This report shares the results of the PER and provides key policy recommendations on how to address the existing challenges.